Avaliação e seleção simultânea do layout e políticas de controle operacionais em armazéns por meio de mcda e sed - Silva, Lucas Eric da (2019)
Strategic decisions such as layout and tactical and operational decisions such as control policies affect warehouse performance criteria (costs, throughput, storage capacity and response time). Once taken, these decisions do not allow an easy alteration due to inconvenience to the operation and the end customer, or physical limitations. Therefore, they should be considered at the design phase and simultaneously, since the combination of their possible alternatives leads to different results. On the other hand, these decisions have a multicriteria aspect involving trade-offs that managers must analyze according to the market in which the company is inserted. Yet, the stochastic behavior of the demand profile, the picking activity congestion and the uncertainties of the scenarios that the operation may face should also be considered in the design phase. Thus, the present work aims to propose a methodology for evaluation and selection of the robust combination between aisle layout and operational control policies (storage, picking and routing) alternatives. The model consists of: (1) a discrete event simulation (SED) model to capture the stochastic character of the operation parameters (order arrival time, order arrival time variation, and order list size), congestion and make a quantitative analysis of the different combinations; (2) a multicriteria decision analysis (or MCDA) model in order to contemplate trade-offs between different criteria and objectives / preferences of decision makers, incorporating scenario planning. The results appear to be useful for small operations and may contribute to the development of new projects considering uncertainties and decision makers' preference. For the academy, the results bring the proposition of a methodology that jointly analyzes decisions at different levels through the combination of methods, previously unused for operations in distribution centers, and which can also serve to foster research from the perspective of distribution logistics.